2004
DOI: 10.1046/j.1365-2141.2003.04736.x
|View full text |Cite
|
Sign up to set email alerts
|

Additional cytogenetic abnormalities in adults with Philadelphia chromosome‐positive acute lymphoblastic leukaemia: a study of the Cancer and Leukaemia Group B

Abstract: Summary We analysed the nature and prognostic significance of secondary cytogenetic changes in 111 newly diagnosed adults with acute lymphoblastic leukaemia (ALL) and t(9;22)(q34;q11.2) or its variants. Secondary aberrations were seen in 75 (68%) patients. They included, in order of descending frequency: +der(22)t(9;22), +21, abnormalities of 9p, high hyperdiploidy (>50 chromosomes), +8, −7, +X and abnormalities resulting in loss of material from 8p, gain of 8q, gain of 1q and loss of 7p. Eighty patients (72%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 75 publications
5
60
4
2
Order By: Relevance
“…This effect was independent of age and WCC, both of which are significantly higher among Ph ϩ patients. In contrast to the CALGB study 31 we did not find heterogeneity of outcome among Ph ϩ patients according to the presence of Ϫ7 or an extra Ph. There are differences between the 2 cohorts and in the methods of analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…This effect was independent of age and WCC, both of which are significantly higher among Ph ϩ patients. In contrast to the CALGB study 31 we did not find heterogeneity of outcome among Ph ϩ patients according to the presence of Ϫ7 or an extra Ph. There are differences between the 2 cohorts and in the methods of analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…As far as concerns t-HeH patients with t(9;22), it has been suggested that they either have a more favorable survival and/or treatment response compared with t(9;22)-positive near-diploid ALL 20,21 or the same dismal outcome as all other patients with this translocation. 22,23 The fact that all six t-HeH with t(9;22) in our Nordic cohort achieved complete remission and all but one remain alive would rather agree with the former view ( Table 2; Online Supplementary Table S1). Obviously, larger series are needed to address this clinically important issue, and this is something that will require international collaboration due to the rarity of t-HeH in pediatric patients.…”
Section: In Cases With 51-67 Chromosomes; 2 Data Missing For Some Varsupporting
confidence: 68%
“…[5][6][7] Apart from the t(9;22)-positive case in this report, the t(9;22) has been reported in association with dic (9;20) in five previous casesFthree adult 1,10,20 and two pediatric BCP ALLs. 6,13 Furthermore, in the only dic(9;20)-positive T-cell ALL reported to date, a t(8;14)(q24;q11) was also present.…”
Section: Discussionmentioning
confidence: 86%